Forty Years of PEAN and Nigeria’s National Policy on Education (2021)
Guidance and monitoring are essential in every human or social endeavour to attain success. Unguided and unmonitored activities are likely to fail hence, the imperative of guidance and monitoring in human activities. Groups, associations and bodies do volunteer to carry out activities of supervision or scrutinizing undertakings of individuals, societies and organisations even without profit motive, all in the spirit of ensuring standards and attaining objectives. The Philosophers of Education Association of Nigeria (P.E.A.N) is an academic body involved in the development and practice of education in Nigeria. As part of her responsibilities to the Nigerian Society in the forty years of her existence, it is pertinent to examine activities of the education sector in order to determine its relevance to the growth aspirations of the country. There are arguments as to the reasons for the alleged failure of Nigeria’s education system; some had attributed it to the attitudes of people in the society, while others claimed it was the policy guidelines. This paper therefore sets out to examine the \national Policy on Education (N.P.E.) as a document to determine its adequacy, relevance or otherwise in the practice and administration of Nigeria’s education system. The Philosophical Research Method (P.R.M.) as well as the Content Analysis (C.A.) mode was adopted to scrutinise the policy document. The paper concluded that funding and implementation of policy guidelines have been the bane of the effective and efficient practice of education. Recommendations were made thereafter.